Power Transmission Congestion Management In Compitative Electricity Market By Price Intrusion Using Soft Computing Technique - Swakantik Mishra, Abhinna Chandra Biswal (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The load dispatch centre is responsible for transporting electricity to consumers, Like urban transportation, transporting electricity is also a challenge. If things are normal as planned then there will be no issues in transporting electricity to consumer from generating stations, but the challenge arises when there is a problem like outage, force outage, unscheduled maintenance issue etc. Every state in India has load dispatch centre, which deals with contingent issues. In this paper we have discussed such issue and provided solution with the help of machine learning techniques on how to do effective transmission congestion management by adopting innovative pricing techniques